The Effect of SiGe/PTAA Thin Film Thickness as An Active Layer for Solar Cell Application - ABDUL ISMAIL ABDUL RANI; Muhammad Afif Abdul Rani, University College of Technology Sarawak; Samat Iderus, University College of Technology Sarawak; Mohd Shahril Osman, University College of Technology Sarawak; Nuramalina Bohari, University College of Technology Sarawak (ASM Science Journal, 2022)
This paper presents the results of electrical simulations at different active thickness layers of hybrid photovoltaic devices using GPVDM software. A combination of inorganic n-type semiconductor SiGe and organic p-type semiconductor PTAA has been chosen to be simulated in this research work. The thickness of SiGe and PTAA varies from 100 nm – 500 nm and 1000 rpm – 5000 rpm. The results show that the thickness of both semiconductor affects the electrical properties. Higher current density, Jsc, can be obtained as the thickness of SiGe increases. PTAA as an active layer had affected the value of open-circuit voltage, Voc. The SiGe combination with lower rpm depicted a higher value of Voc than the other combinations. The FF and efficiency rate of the solar panel is also presented in this work. This research focuses on the thickness combination of both semiconductors layer on the performance of its electrical characteristics.